Doing visual research - Mitchell, Claudia (Los Angeles : SAGE, 2011)
This work offers an introduction to the use of photography, collaborative video, drawing, objects, multi-media production and installation in research. The author explains how visual methods can be used as modes of inquiry as well as modes of representation for social research. The book looks at a range of conceptual and practical approaches to a range of tools and methods, while also highlighting the interpretive and ethical issues that arise when engaging in visual research. She draws on her own work in the field of visual research throughout to offer extensive examples from a variety of settings and with a variety of populations. Topics covered include: Photographs and memory work studies; Drawing as a participatory visual methodology; Working with images, Writing about images; Can visual methods make a difference? : from practice to policy. This book takes an interdisciplinary approach to the subject of visual research, producing a practical introduction to the subject.
Getting the Picture. On a pedagogy of ethics in visual research: who's in the picture? -- Visual Methods for Social Change: Tools and Techniques. Not just an object: working with things, objects and artefacts in visual research ; Seeing for ourselves: a case for community-based photography; Community-based video-making -- On Interpreting and Using Images. Working with photo images: A textual reading on the presence of absence -- Data collections and building a democratic archive: "No more pictures without a context" (with Naydene de Lange) -- Look and see: images of image making -- What can a visual researcher do with a camera? -- Changing the picture: how can images influence policy-making?
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Visual sociology -- Research; Electronic books